PREVALENCE OF URINARY TRACT INFECTION AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINIC AT KASANGATI HEALTH CENTER IV IN WAKISO DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Kinene Enock; Margret Nakalema (Student's Journal of Health Research, 2023)
Background: Urinary tract infections (UTIs) are a common bacterial infection among pregnant women affecting up to 10% of pregnant women worldwide. Despite the increase and availability of UTIs in Uganda, the prevalence is still unknown. Therefore this study aimed at determining the prevalence of UTI, most affected age and risk factors associated with UTI among pregnant women attending the antenatal care clinic at kasangati health center IV in Wakiso district. Methodology: The study employed a descriptive cross-sectional study both quantitative methods. The results were obtained through laboratory diagnosis of midstream urine. Data collected from the study were analyzed using SPSS version 2.0 and presented on tables and graphs. Results: The most affected age group in terms of UTIs is the 23-27 years category, with 36.9% of pregnant women having had UTIs. The 28-32 years category follows closely behind, with 32.9% of pregnant women having UTIs. The other age groups have lower percentages of UTI occurrences. pregnant that were single had a higher percentage of UTI cases (87.5%), (81.5%) among housewives, (79.5%) resided in urban areas, (87.5%) among Muslim pregnant women, and a higher percentage of UTI cases (83.9%) occurred among those with higher incomes (>50,000/=). pregnant women with multiple partners, changing undergarments once a day, knowledge about UTI cases and UTIs from sex, using contaminated toilets, cleaning directions, and frequency of weekly sexual intercourse. Conclusion: The study recorded a higher prevalence (73%) of UTIs in pregnancy than in all the studies. Recommendation: The study recommended that the introduction of culture and sensitivity for every pregnant woman especially those with a history of UTI should be considered as well as made available at least at health center IV hospitals since it acts as referral point to several pregnant women.